Modelling Runoff on a Small Lowland Catchment, Hungarian Great Plains - Právetz, Tamás; Sipos, György; Benyhe, Balázs; Blanka, Viktória (Journal of Environmental Geography, 2015)
The lowland region of the South-Eastern Carpathian Basin faces extreme hydrological conditions, therefore the more detailed understanding, monitoring and predicting of the hydrological regime on catchments have high importance. However, in the region only few measured data are available in terms of evaporation, runoff, infiltration and water retention, and this is especially true concerning small catchments. In the meantime these areas support extensive agriculture, therefore more information is needed to manage future drying and irrigational demands. In the present research runoff and discharge were modelled for a ten year period and compared to at-a-station measurement data on the Fehértó-majsa Canal, a sub-catchment of the Tisza River, in order to test the predictability of hydrological changes related to future climate change. Modelling was made by applying a coupled MIKE SHE/MIKE 11 model and integrating all available topographic, pedologic, climatic, hydrologic and vegetation data. Consequently, another motivation of the research was to assess the suitability, data demand and limitations of the MIKE modelling environment on lowland catchments. As from all available data sources soil data seemed to be the least accurate, sensitivity tests were made by changing different soil parameter. Based on the results, the developed model is highly suitable for the estimation of annual and monthly runoff. Nevertheless, concerning daily data a general overestimation of discharge was experienced during low flow periods, and a time lag appeared between measured and modelled discharge peaks during high flow periods. In all, the results of the study can greatly support the realization of water management and planning projects in the drought prone sand land catchments where only a few directly measured data are available.